2012
DOI: 10.1080/13607863.2012.660620
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about Alzheimer's disease in Britain

Abstract: Respondents revealed knowledge gaps pertaining to conditions that masquerade as AD, increase ones vulnerability to AD, and exacerbate AD symtomatology. Educational campaigns that specifically target these issues may help reduce the impact of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
3
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 18 publications
9
40
3
7
Order By: Relevance
“…While several studies have investigated knowledge of methods to reduce dementia risk, most have used prompted, closed questions [34,51,52] which may overestimate knowledge prevalence due to the possibility of correct guessing [53]. The unprompted knowledge question used here found that undertaking mentally stimulating activities was the most widely identified activity that a person could do to reduce dementia risk, which is consistent with the findings of several previous studies [35,36,52].…”
Section: Discussionsupporting
confidence: 84%
“…While several studies have investigated knowledge of methods to reduce dementia risk, most have used prompted, closed questions [34,51,52] which may overestimate knowledge prevalence due to the possibility of correct guessing [53]. The unprompted knowledge question used here found that undertaking mentally stimulating activities was the most widely identified activity that a person could do to reduce dementia risk, which is consistent with the findings of several previous studies [35,36,52].…”
Section: Discussionsupporting
confidence: 84%
“…Factor analysis supported the use of a total score on the ADKS to reflect overall knowledge of AD. The ADKS has been employed by other researchers to examine accuracy of knowledge of AD (Hudson, Pollux, Mistry, & Hobson, 2012;Nordhus, Sivertsen, & Pallesen, 2012).…”
Section: Alzheimer's Disease Knowledge Scalementioning
confidence: 99%
“…A recent review [7] of such tools concluded that while the Alzheimer’s Disease Knowledge Test (ADKT) [17] was the oldest and most widely used, a more recent tool, the Alzheimer’s Disease Knowledge Scale (ADKS) [18], was promising and showed good psychometric properties. Originally only used by its developers [19], two recently published articles have confirmed the utility of the ADKS in this context [20,21]. Assessing the level of dementia knowledge among health professionals is important to: assess the level of knowledge prior to the implementation of dementia knowledge programs as a baseline; identify the gaps in knowledge to be included in a program; and then to assess the effectiveness of a dementia knowledge education program [2,6,7,12,22].…”
Section: Introductionmentioning
confidence: 99%